Magnetic bead-based AuNP labelling combined with inductively coupled plasma mass spectrometry for sensitively and specifically counting cancer cells. Issue 3 (22nd December 2015) - Yang, WeiJuan; Xi, Zhiming; Zeng, Xiaoxue; Fang, Ling; Jiang, Wenjing; Wu, Yongning; Xu, LiangJun; Fu, FengFu
Abstract : A novel method for sensitively and specifically counting cancer cells using a MB-based AuNP–aptamer labelling technique and ICP-MS detection is presented in this study. Abstract : Early diagnostic methods are the most effective way to increase the survival rate of cancer patients. In this study, we present a novel method for sensitively and specifically counting cancer cells using a magnetic bead (MB)-based AuNP–aptamer labelling technique and inductively coupled plasma mass spectrometry (ICP-MS) detection. A MB-based AuNP–aptamer labelling technique can specifically recognize cancer cells and tag AuNPs to the cancer cells, which provides a platform for indirectly counting cancer cells via the detection of Au with ICP-MS. The method reported in this study combines the merits of a MB-based AuNP–aptamer labelling technique and ICP-MS detection, resulting in better specificity and stability, high sensitivity, short analysis time, and robust resistance to a complicated matrix. Especially, the employment of ICP-MS detection and the presence of MBs that facilitate the magnetic separation of target cells, not only greatly shorten the analysis time but also greatly enhance the resistance of our method to a complicated matrix. The proposed method can be used to count as few as 100 human hepatocellular carcinoma SMMC-7721 cells in 1 mL of serum with a recovery of 93–104% and a RSD < 4% ( n = 5) within 3 hours. The success of this study provides a promising rapid approach for the early detection of human hepatocellular carcinoma cells in clinical diagnosis.